Kajian Fenomenologi terhadap Perubahan Budaya Akulturatif di Sumenep Madura - Ahyani, Shidqi (Islamika Inside: Jurnal Keislaman dan Humaniora, 2021)
Abstract: The religious behavior of the Muslim community cannot be separated from local traditions that run in societies where social interaction. However, in its development, some local traditions are permanent and some have undergone several changes. This study intends to reveal the cultural changes in the acculturation of Islam and local culture in Sumenep Madura, with a sub focus that includes: the factors that underlie the change and the form of cultural change. This type of research is qualitative with a phenomenological approach. Sources of data in this study consisted of religious figures, community leaders, and cultural figures in Sumenep district as the main sources. Data collection was carried out by means of in-depth interviews and participatory observation. The data analysis method used was the Stevick-Colaizzi-Keen phenomenology. The results showed that the factors underlying the occurrence of cultural changes in the acculturation of Islam and local culture were: contact with Islamic culture, a more advanced education system and a less than perfect process of traditional inheritance. The forms of cultural change are small changes and changes that are planned.